Stories of Hope and Health: Wisdom From Older Mexican–American Women Who Broke Free From the Entangled Web of Love and Violence - Divin, Chris A. (Violence against women, 2023)
This interpretive qualitative study explores the lived experience of intimate partner violence (IPV) among 12 older Mexican–American women aged 55–85 with past experiences of IPV to understand how it shaped their lives. Sociocultural factors that influenced the IPV experience and sustained health amidst adversity were explored. Denzin’s interpretive interactionism along with Antonovsky’s salutogenic theory guided this study. These women survived IPV and discovered ways to foster health and thrive in later years. They all vowed to break the cycle of violence for future generations. Their wisdom offers hope and has implications for healthcare professionals, future research, and advocacy efforts.